Memórias escolares e trajetória de vida de pessoas com deficiência visual à luz da Teoria da Autodeterminação - Alves, Gislene de Araújo (2021)
The thesis presents the main motivational factors of the person with visual impairment throughout their school trajectory and in the different formative dimensions, in which we seek to understand what are the school relationships and interrelations that constitute the process of personal and professional training that provide the development of basic psychological needs (autonomy, competence and belonging or social bonds) of the collaborators participating in this research. As empirical material, we work with autobiographical narratives, which were collected through interviews with five participants, adults, visually impaired, blind, and with low vision and higher education. For the interpretative analysis of autobiographical narratives, we used the Theory of Self-Determination by Ryan and Deci (1985; 2000; 2017) identifying the basic psychological needs (autonomy, competence, and belonging) in which we analyzed the main motivational factors identified in the participants' memories. This study recognizes that school memories as a fertile field that makes us understand and reflect on the relevance of socio-educational relationships for the life of the visually impaired person, in addition to indicating that the visually impaired person develops (self) learning strategies that strengthen the levels of autonomy, competence and belonging in their social relationships throughout life, and especially, throughout school life. Throughout the analysis, we realized that memories had a structural organization, which led us to the studies of Labov (1972) and that we were inspired to reveal these organizations. Through the structural identification of the narratives, we observe that there are four dominant categories: the family, the school, the disability, and the profession. Some narratives present narrative points in which they bring memories with parental reminiscence (origin), intrinsic memories (experiences lived by the narrator). Disability, even appearing at the origin of the narrative, becomes the main complicating factor and goes through evaluative transitions of the narrator until reaching the point of resolutions (set of events associated with the complicating factor). It is concluded that the person with disabilities has several motivational factors to overcome the challenges faced during school / academic and professional life, with the family being the main source of support for maintaining the motivations and meanings of autonomy and competence, then the school environment emerges as an environment that provides the sense of belonging and the expansion of social bonds, followed by academic life at a higher level, in which it brought the challenges of accessibility and adaptation that helped in the development of strategies to maintain the subject's motivation in relation him and the course. Finally, the arrival in the professional career, in which we identify the choice for the profession through the identified extrinsic motivation and/or introjected extrinsic motivation. We observed that the limits and prejudices about visual impairment and the meanings of autonomy, competence, and social bonds impelled the subjects of this study to reach their personal and professional achievements.